1969
DOI: 10.1139/p69-114
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic study of HCP, the phosphorus analogue of hydrocyanic acid

Abstract: The ultraviolet absorption spectrum of HCP has been observed from 4100 Å to about 2350 Å, and seven electronic transitions have been identified. Three of these transitions involve excited singlet states and four of them involve excited triplet states. The symmetries, energies, and equilibrium conformations of these states are listed below:[Formula: see text]Some observations have also been made on the vibration–rotation energy levels of the ground electronic state, [Formula: see text], of HCP. The fundamental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 0 publications
3
22
0
1
Order By: Relevance
“…4. The possibility exists 6 however, there is reasonable agreement in the vibrational frequencies. The angles differ greatly but the CP bond length exhibits excellent agreement with the experimental values.…”
Section: Lowest 1 ⌬ State Of Hcpmentioning
confidence: 87%
See 4 more Smart Citations
“…4. The possibility exists 6 however, there is reasonable agreement in the vibrational frequencies. The angles differ greatly but the CP bond length exhibits excellent agreement with the experimental values.…”
Section: Lowest 1 ⌬ State Of Hcpmentioning
confidence: 87%
“…The second singlet excited state ͑B ͒, considered by Johns et al 6 to be a 1 ⌸ state, was reexamined in 1972 by Moehlmann et al 7 in a study exploiting the Zeeman effect. The group found that the Zeeman splitting for the B state increased as the rotational quantum number J increases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations